Novel imaging modalities for the identification of vulnerable plaques - Wang, Ziyan; Zhang, Pingyang (Frontiers in Cardiovascular Medicine, 2024)
Atherosclerosis is a slow, progressive disease that is closely associated with major adverse cardiovascular events. Early diagnosis and risk assessment of atherosclerosis can effectively improve the prognosis and reduce the occurrence of adverse cardiovascular events in the later stage. A variety of invasive and non-invasive imaging modalities are important tools for diagnosing lesions, monitoring the efficacy of treatments, and predicting associated risk events. This review mainly introduces the four commonly used non-invasive imaging modalities in clinical practice and intravascular imaging such as optical coherence tomography, intravascular ultrasound imaging, and near-infrared spectroscopy, compares the advantages and disadvantages in the diagnosis of vulnerable plaques, and briefly summarizes the new progressions of each.